E-Government dan Reformasi Birokrasi dalam Rangka Peningkatan Pelayanan Publik di Daerah - Putra, Roni Ekha (Jurnal Demokrasi, 2009)
Utilization of information technology in providing public services to the community is a very important nowadays, considering the time of the development was faster. Developing information technology has caused no clear boundaries between one States with other countries in the world. For now, how is local government able to utilize the facilities and infrastructure of information technology to provide prime services to the community. So that service can be provided easily, quickly, and precisely. This paper will describe about information technology utilization that able to provide changes in the public service bureaucracy that is in the area so that services can be enjoyed by the whole society. Â  Kata Kunci: Pelayanan Publik, Teknologi Informasi, Birokrasi, Reformasi Birokrasi